(untitled) (Revista Científica Integrada, 2023)
In this editorial, PhD in Nursing, Luciane Ferreira do Val, brings reflections aimed at nurses, coming from a paranymph speech, given at the degree award ceremony of a class of the Bachelor of Nursing course. With mentions of the work by Rubem Alves, entitled Ostra Feliz Não Faz Pérola, the author mentions that pearl nurses are transformed into the capacity for continuous astonishment at the potentialities of life that are being remade.